Impact of Prostate Needle Biopsy on Erectile Function - Fatih Yanaral; Faruk Özgör; Metin Savun; Ali Ayrancı; Ufuk Çağlar; Alkan Çubuk; Ömer Sarılar (Haseki Tıp Bülteni, 2019)

(untitled)
Aim:To evaluate the impact of transrectal ultrasonography-guided prostate needle biopsy (TRUS-Bx) on erectile function.Methods:Patients who underwent TRUS-Bx were prospectively examined. The indications for prostate biopsy were elevated prostatespecific antigen (PSA) level and/or abnormal digital rectal examination. All patients were evaluated with the 5-item version of the International Index of Erectile Function (IIEF-5) before TRUS-Bx and at one, three and six months after TRUS-Bx. Severity of erectile dysfunction (ED) was classified into five categories according to IIEF-5 scores.Results:Eighty patients were included in the study. The mean age of the patients was 64.7 years and the mean serum PSA level was 10.2 ng/mL. The mean IIEF-5 score was 16.5 prior to TRUS-Bx. Before TRUSBx, ED was reported in 61 patients and mild, mild to moderate, and moderate ED in 23 (28.8%), 21 (26.2%), and 17 (21.2%) patients, respectively. Six months after TRUS-Bx, ED was reported as mild, mild to moderate, moderate and severe in 23 (28.8%), 21 (26.3%), 16 (20%) and one (1.3%) patients, respectively. The differences between before and after prostate biopsy were statistically insignificant (p>0.05).Conclusion:TRUS-Bx does not have a permanent effect on erectile function. It seemed to be a trend toward increasing ED at 1 month and longer follow-up showed that these changes resolved back to baseline.